2015
DOI: 10.1016/j.immuni.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Mouse Bone Marrow Cultures Comprise a Heterogeneous Population of CD11c+MHCII+ Macrophages and Dendritic Cells

Abstract: Dendritic cells (DCs) are key players in the immune system. Much of their biology has been elucidated via culture systems in which hematopoietic precursors differentiate into DCs under the aegis of cytokines. A widely used protocol involves the culture of murine bone marrow (BM) cells with granulocyte-macrophage colony-stimulating factor (GM-CSF) to generate BM-derived DCs (BMDCs). BMDCs express CD11c and MHC class II (MHCII) molecules and share with DCs isolated from tissues the ability to present exogenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
722
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 681 publications
(791 citation statements)
references
References 50 publications
58
722
9
2
Order By: Relevance
“…The GM-CSF-expanded DCs were 85-90% CD11C + , and 45% were CD11c + MHC class II high . This finding is consistent with the recent demonstration that GM-CSF-expanded BMDCs are a heterogeneous population of DCs and monocytederived macrophages (21). Indeed, we found that FHES also enhanced TGF-b production by FLT3L-expanded BMDCs and M-CSF-expanded macrophages (data not shown), suggesting that FHES induces anti-inflammatory cytokine production by macrophages and DCs.…”
Section: Role Of Regulatory Cytokines and Cells In The Immunosuppresssupporting
confidence: 93%
“…The GM-CSF-expanded DCs were 85-90% CD11C + , and 45% were CD11c + MHC class II high . This finding is consistent with the recent demonstration that GM-CSF-expanded BMDCs are a heterogeneous population of DCs and monocytederived macrophages (21). Indeed, we found that FHES also enhanced TGF-b production by FLT3L-expanded BMDCs and M-CSF-expanded macrophages (data not shown), suggesting that FHES induces anti-inflammatory cytokine production by macrophages and DCs.…”
Section: Role Of Regulatory Cytokines and Cells In The Immunosuppresssupporting
confidence: 93%
“…As illustrated in Figure 1C neg cells (Supplemental Figure 1B), which resemble the macrophage/monocyte population described by Helft et al (30). Injection of blood MoDC or TADC loaded with alloIgG-IC into the tumor-resected mice from which they were derived failed to protect against tumor recurrence ( Figure 1D).…”
Section: Alloigg-ic-loaded Bmdc But Not Tadc or Modc Prevent Tumor supporting
confidence: 58%
“…Unexpectedly, we showed that CD9 deficiency did not affect Ag presentation by Flt3L-dependent conventional BMDCs. Recently, it has been suggested that BMDC cultures generated with GM-CSF are heterogeneous, containing CD11c ϩ MHC-II ϩ conventional DCs and monocyte-derived macrophages (63). GM-CSF-dependent BMDCs resemble monocyte-derived DCs (MoDCs), which constitute specialized inflammatory DCs, although monocytes can also be precursors of different DC subsets under steady-state conditions (53,54).…”
Section: Discussionmentioning
confidence: 99%